Local and global environmental drivers of growth chronologies in a demersal fish in the south-eastern Pacific Ocean - Guillermo Moyano (Elsevier, 2021)
Upwelling and the El Niño “Southern Oscillation” (ENSO) are recurrent climatic phenomena in the southeastern Pacific Ocean that severely affect the reproduction and growth of pelagic fish populations. However, there are not long-term growth data from demersal fish populations to test these interconections in a long-term analysis. For this reason, a first extensive growth chronology was reconstructed from the annual growth of sagittal otoliths as a proxy for somatic growth for the cardinalfish (Epigonus crassicaudus). Adult fish ranging from 35 to 40 cm in fork length and from 39 to 63 years in age were collected off Chilean waters. The master chronologies were estimated for the period from 1974 to 2014, using the regional curve standardization approach (RCS) and linear mixed models (LMMs). Growth indexes derived from both approaches followed a similar trend and were positively correlated with the Humboldt Current Index (HCI) and negatively with ENSO, Pacific Decadal Oscillation and sea surface temperature. LMMs showed that a 75% of growth variability was explained by the age of increment formation and HCI was the environmental index that most significantly affected the annual growth of cardinalfish followed by the sea surface temperature in spring. A reduced growth phase from 1974 to 1996 contrasted with a higher growth period from 1997, matching the 1997/1998 climatic regime shift, demonstrating that the enhanced growth for cardinalfish was associated with upwelling of nutrient rich water to the surface, triggering an increase of the primary and secondary productivity during the prevalence of a cold regime period in the Humboldt Current System. The consistence between RCS and LMM methods was indicative that both approaches are promising to evaluate the influence of environmental drivers on the growth condition of a demersal fish population in a highly productive marine ecosystem.